رؤية تجريدية للعناصر الأدمية في النحت الخزفي باستخدام ملامس الخامات البيئية السعودية - إسكندر، نقار عبدالباقي (جامعة حلوان - كلية التربية الفنية, 2013)
يتضمن موضوع الدارسة والخلفية ومشكلة البحث وأهميته و أهدافه و فروضه و بالإضافة إلى الحدود والمنهج المتبع والمصطلحات . \ تناول البحث نشأة وتاريخ المنحوتات الخزفية المجردة في بعض الحضارات مع توضيح مفهوم المنحوت الخزفي المجرد من خلال التعرف على مفهوم كل من فن النحت و فن الخزف مع ذكر بعض العوامل التي ساعدت على ظهور المنحوتات الخزفية المجردة مثل التقدم العلمي لتكنولوجي ، الثورة الصناعية و انتشار الآله ، وتعدد الخامات والأدوات ، وحركة الفنون المستحدثة والزخرفيه ، وظهور مفاهيم جديدة لفن التعبير المجسم . \ وقد قدمت فيه الدارسة أهمية الملمس في تكوين المنحوت الخزفي ودوره في تأكيد البعد الجمالي، حيث قامت الدارسة بتجارب عملية بإستخدام بعض عناصر البيئة السعودية في تشكيل أعمال نحتية خزفية مبتكرة والاستفادة من استخدام العناصر المختلفة في البيئة السعودية وحتى يكون الملمس مصدر أساسي في تشكيل المنحوت الخزفي . \ أنهت الباحثة البحث بعرض بعض النتائج بالإضافة إلى التوصيات والمراجع This research addresses the Creation of Abstract human figures Ceramic Sculptures with varied Textures from Saudi Environment Substances \ The research contains the subject of the study, its background, the problem, hypothesis, objectives, and importance of the research, in addition to the limits, methodology, terminology and related studies. \ Then follows the origins and history of abstract ceramic sculptures in some civilizations, explaining the concept of abstract ceramic sculpture. That is through the identification of the concepts of both the art of sculpture and the art of ceramic, mentioning some factors that have helped the emergence of abstract ceramic sculptures, such as scientific and technological progress, and the spread of machine industrial revolution, and multiple materials and tools, and the movement of developed and decorative arts, and the emergence of new concepts of three-dimensional expression. \ It Deals with ceramic sculpture and the varied textures in Saudi environment; that is through specifying the types and texture properties of it, with recognition of different elements together with some properties and ways of forming abstract ceramic sculpture, organic or geometric, in addition to the principle bases of its modeling. That is to show the linkage between the textures and abstract ceramic sculpture, in terms of formal relationship of texture as plastic treatment and the tacit relationship of texture as a plastic element and aesthetic value. \ Rresearcher concluded by presenting some meaningful results as well as the recommendations and references.
Keywords: النحت -- النحت الخزفي -- الخامات البيئية -- السعودية